Self-Perceived Impact of Oral Health on the Quality of Life of Women Deprived of Their Liberty - Ludmila Roberto Moraes; Lidiane Castro Duarte de Aquino; Danielle Teles da Cruz; Isabel Cristina Gonçalves Leite (Hindawi Limited, 2021)
Background. Prison units are marked by structural deficiencies, especially in relation to the female gender. Objectives. To measure the self-perceived impact of oral health on the quality of life of Brazilian women in detention. Methodology. A survey was carried out conducted in the penitentiary at Juiz de Fora (Minas Gerais, Brazil) using an instrument with semistructured questions and validated scales, including the Oral Health Impact Profile-14. 99 women were interviewed. The analysis was based on a theoretical model of determination, with hierarchical blocks of variables. Bivariate analysis was done using the Mann-Whitney, test and multivariate analysis was used using linear regression. The significance level was set at 5%. Results. 33% experienced tooth loss after incarceration, (3.70 ± 3.26 lost teeth). 65.6% rated the dental service as fair/poor. The highest prevalence of oral health impact was for the domains of psychological discomfort (50.5%) and physical pain (40.4%). There is a negative impact on psychological discomfort: the number of dental consultations in the past year and self-perceived general health. There is an impact on physical pain: self-declared color and anxiety. Self-perceived general health had an impact on the domains of psychological disability and social disadvantage. Depression had an impact on the total score. Conclusion. This study revealed a self-perceived impact of oral health on the quality of life of women inmates. We need to ensure high-quality access to dental treatment in prisons.